The Role of NAG-1/GDF15 in the Inhibition of Intestinal Polyps in APC/Min Mice by Sulindac - Wang, Xingya (2011)
The antitumor effects of nonsteroidal anti-inflammatory drugs (NSAID) are assumed to be due to the inhibition of COX activity, but COX-independent mechanisms may also play an important role. NSAID-activated gene (NAG-1/GDF15) is induced by NSAIDs and has antitumorigenic activities. To determine the contribution of COX-2 inhibition and NAG-1/GDF15 expression to the prevention of colon carcinogenesis by NSAIDs, we evaluated several sulindac derivatives [des-methyl (DM)-sulindac sulfide and its prodrug DM-sulindac] that do not inhibit COX-2 activity. Sulindac sulfide and DM-sulindac induced the expression of NAG-1/GDF15 in HCT116 cells as determined by quantitative real-time PCR and Western blot. We fed APC/Min mice with 320 ppm of sulindac and doses of DM-sulindac. Only sulindac significantly inhibited tumor formation in APC/Min mice. To determine the pharmacokinetic properties of sulindac and DM-sulindac in vivo, wild-type C57/B6 mice were fed with sulindac and DM-sulindac at 80, 160, and 320 ppm. High-performance liquid chromatography analysis revealed that the conversion of DM-sulindac to DM-sulindac sulfide (active form) was less efficient than the conversion of sulindac to sulindac sulfide (active form) in the mice. Lower levels of DM-sulindac sulfide accumulated in intestinal and colon tissues in comparison with sulindac sulfide. In addition, NAG-1/GDF15 was induced in the liver of sulindac-fed mice but not in the DM-sulindac–fed mice. Collectively, our results suggest that the tumor-inhibitory effects of sulindac in APC/Min mice may be due to, in part, NAG-1/GDF15 induction in the liver. Our study also suggests that pharmacologic properties should be carefully evaluated when developing drug candidates.